PENERAPAN BATAS MINIMUM DAN MAKSIMUM KECEPATAN KENDARAN DI RUAS JALAN TOL BERDASARKAN PASAL 3 AYAT (4) PERATURAN MENTERI PERHUBUNGAN REPUBLIK INDONESIA NOMOR PM 111 TAHUN 2015 TENTANG TATA CARA PENETAPAN BATAS KECEPATAN (STUDI KASUS JALAN TOL PEKANBARU-DUMAI) - Meylyn Meylyn; Gusliana HB; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
This research relates to the Minimum and Maximum Speed Limits ofVehicles Based on Article 3 Paragraph (4) of the Regulation of the Minister ofTransportation of the Republic of Indonesia Number PM 111 of 2015 concerningProcedures for Setting Speed Limits (Case Study of the Dumai-Pekanbaru TollRoad). Road traffic and transportation as part of the national transportationsystem must develop its potential and role to realize security, safety, order andsmooth traffic and road transportation in order to support economic developmentand regional development. Road traffic and transportation safety is a condition inwhich everyone is protected from the risk of accidents during traffic caused byhumans, vehicles, roads and/or the environment. But in reality, theimplementation of this regulation is still experiencing some obstacles.This type of research is sociological law, namely research that wants tosee the correlation between law and society, so as to be able to reveal theeffectiveness of the enactment of law in society. This research was conducted atPT. Hutama Karya (HK) Pekanbaru-Dumai and the Riau Regional Police TrafficDirectorate. Sources of data used are primary data and secondary data. Datacollection techniques in this study were interviews and literature review andconcluded with deductive thinking methods.From the results of the study it was concluded that first, the Minimum andMaximum Limits for Vehicle Speed Based on Article 3 Paragraph (4) of theRegulation of the Minister of Transportation of the Republic of Indonesia NumberPM 111 of 2015 concerning Procedures for Setting Speed Limits have not beenimplemented properly. Second, the factors that affect violations of the maximumspeed limit on the Pekanbaru-Dumai toll road are the human factor and thevehicle factor. Third, the efforts of PT. Hutama Karya and the Riau Police TrafficDirectorate are installing traffic signs, taking action against traffic offenders onthe toll road, and advising all motorists to always check the condition of theirtires and comply with the set speed on the toll road.Keywords: Implementation- Speed Limit